Myths and Misconceptions of Covid-19 Vaccination in Women of Reproductive Age - Lubna Riaz Dar (Shalamar Medical & Dental College, Lahore, Pakistan, 2022)
Myths and Misconceptions spread very fast as compared to facts in the current situation of social connectivity. The same is about Covid-19 infection and its vaccine in women of reproductive age and in pregnancy. We need to correct these misconceptions with evidence which is the objective of this editorial about covid vaccination.